Teaching Writing Recount Text For The Second Year Students Of SMP Negeri 2 Banyudono In 2012/2013 Academic Year (A Descriptive Study) - Pertiwi, Yulianti Dian, Drs. Djoko Srijono, M.Hum, Dra. Dwi Haryanti, M.Hum (2013)
This study aimed at describing teaching writing recount text at the second year of SMP N 2 Banyudono in 2012/2013. This research applies descriptive qualitative research and a classroom action research. In collecting data the writer used interview, observation, and documentary as the innstrument of writing teaching -learning process. The data were analyzed by (1) make summary from the main points and categorizes based on the clasification, (2) analyzes the data (3) give verification and write conclusion. The result shows that the teacher used inquiry-based method in teaching learning process, this method focuses on vocabulary implemented in writing class. The implementation has been conducted to the second year students of SMP N 2 Banyudono. The teacher faced some problems in teaching process. The problems were the difficulty in improving the students' vocabulary, different capability of the student and limitation of time. The student's ability in writing recount text is good, because the score is upper the passing grade.